EFEKTIVITAS PAJAK RESTORAN DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH PADA KABUPATEN MAGELANG Tahun 2010-2020: RESTAURANT TAX EFFECTIVENESS IN THE EFFORT TO INCREASE REGIONAL ORIGINAL INCOME IN MAGELANG REGENCY 2010-2020 - Laily Nur Fitriani; Nuwun Priyono; Agustina Prativi Nugraheni (Universitas Sains dan Teknologi Komputer, 2022)
This study was done to determine the impact of the restaurant tax on Magelang Regency's local revenues. In 2010-2020, the descriptive quantitative approach is utilized to analyze restaurant tax target data, restaurant tax revenue realization data, and local revenue realization data. The research data consist of primary data in the form of notes on financial records and secondary data collected from BPPKAD Magelang Regency via observation, interviews, and documentation. The analysis reveals that the amount of efficacy of restaurant tax realization in 2010-2020 fluctuates significantly, with the maximum level of effectiveness occurring in 2014 at 148.49 percent. 2011 was the year with the lowest restaurant tax effectiveness, at 96.75 percent. The 2019 fiscal year had the biggest contribution to municipal revenue from restaurant tax at 4.54 percent, while the 2010 fiscal year had the lowest contribution at 1.92 percent.